Incontinência urinária de esforço: análise de conceito - Thomazini, Janaina Ornelas (2011)
Urinary Incontinence (UI) is considered to be a global problem that affects both men and women. Among the existing types of the condition, the Stress Urinary Incontinence (SUI) is more evident, given its expressive prevalence. The SUI is categorized as a nursing diagnosis (ND) according to the North American Nursing Diagnosis Association International (NANDA-I), a situation that highlights the importance of study development in this area by nurses. The general objectives of this paperwork are: to perform a concept analysis of the stress urinary incontinence, and to compare the concept analysis results to the nursing diagnosis Stress urinary incontinence presented at NANDA-I taxonomy II. The concept analysis was preformed based on Walker and Avant (2005). A literature review was performed on the PubMed, CINAHL and LILACS databases. 810 studies were identified, among which 34 studies that included all the necessary elements for the concept analysis were chosen to comprise the sample. In order to identify the concept uses, textbooks on urology and materials obtained through websites of professional associations were consulted. The concept analysis allowed us to point out that the SUI concept is used mainly in the health services area. The comparison to NANDA-I s SUI nursing diagnosis led to the suggestion that other studies ought to be carried out in order for the definition to be changed to: Involuntary leakage of urine during activities that increase intra-abdominal pressure, without detrusor contraction Suggested adaptations have been made to the existing defining characteristics, with the inclusion of: reported involuntary urine leakage during sexual intercourse (climacturia and/or during penetration); observed or reported involuntary urine leakage during pregnancy; urine leakage during stress test (Valsalva Maneuver, Cough Test and Stress Test at supine position); specific alterations at the urodynamic test (such as lower maximum urethral closing pressure; lower leakage pressure upon stress). Regarding the related factors, we suggest that the term weakening be replaced with dysfunction on the related factor weakening of the pelvic floor muscle . Also among the related factors, we suggest the inclusion of: levator ani muscle dysfunction; pudendal nerve dysfunction; and bladder neck hypermobility and/or urethral hypermobility. The consequences also reflect upon the social and psychological aspects of an individual, resulting in life quality impairment. Empirical references or possible methods for SUI diagnosis confirmation are mainly: history, detailed physical examination and urodynamic tests to identify the exact cause. This study indicates the possibility of contributions to NANDA-I Stress urinary incontinence diagnosis, and provides nurses with support for a better understanding of the matter, which may contribute to a more effective approach of the care planning aimed at patients that present this condition.